Growth Measurement of Some Amylolytic Bacillus Species in Three Media: Growth Measurement of Some Amylolytic Bacillus Species (Biological Sciences - PJSIR, 2009)
Study of the growth pattern of some Bacillus species on starchy substrates showed that the metabolic activity affected the enzymatic activity. B. subtilis (WBS), B. licheniformis (WBL) and B. coagulans (MBC) generally had higher growth rate. B. circulans (SBC) and B. coagulans (WBC) had higher growth on cornstarch medium with corresponding higher b-amylase production as compared to other strains such as B. polymyxa. Ten of the 13 Bacillus species studied had better performance on cornstarch than on soluble starch except B. macerans (MBM), B. macerans (SMB2) and B. subtilis (WBS). The enzyme production ranged from 0.022 unit/cfu x 102 to 0.912 unit/cfu x 102 on cornstarch and 0.01 unit/cfu x 102 to 0.693 unit/cfu x 102 on soluble starch. Relatively higher â-amylase activity was observed in B. subtilis, B. licheniformis,• macerans and B. circulans (WBC1).